Cultivation of lilium a remunerative enterprise in Himachal Pradesh - Dhiman, M R; Kumari, Meenu; Kumar, Raj; Kumar, Sandeep; Singh, S K; Sindhu, S S (Indian Horticulture, 2019)
Lilium has been recognized as a high-value bulbous cut flower crop. Flower growers have shown great interest in its cultivation especially in Himachal Pradesh. It has beautiful attractive flowers of different colour and remains fresh for 7-12 days at room temperature. Its plants forced for year round flowering in polyhouse. Its cultivation has been taken up as commercial venture in open as well as protected conditions in Kullu, Solan, Kangra, Lahaul and Spiti districts of Himachal Pradesh, since it gives high benefit-cost ratio (2.54:1) and is more profitable enterprise to the farmers of hilly regions.